Development of Sparkol Videoscribe Learning Media to Improve Drawing Skills in Illustration Sketch Subjects at SMK Mechanics Cibinong - Restu Urbasyah; Widyasari; Muktiono Waspodo (International Journal of Instruction and Smart Education, 2023)
This study aims to develop digital learning media in the form of Videoscribe Sparkol in learning valid and effective illustration sketches, and can improve students’ illustration drawing skills on cartoon drawing materials. The development of Sparkol videoscribe learning media follows the ADDIE development model. The subjects of the study were material experts, instructional design experts, and learning media experts as well as students of SMK Mechanic Cibinong. The samples in this study were class X DKV 1 as an experimental class and class X DKV 2 as a control class. The findings of this study show that it shows that this videoscribe Sparkol learning media has been feasible and effective and can facilitate the ability to draw illustrations.